2010
DOI: 10.1007/s10924-010-0258-0
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Cellulose Acetate-Based Materials: A Review

Abstract: Cellulose acetate polymer is used to make a variety of consumer products including textiles, plastic films, and cigarette filters. A review of degradation mechanisms, and the possible approaches to diminish the environmental persistence of these materials, will clarify the current and potential degradation rates of these products after disposal. Various studies have been conducted on the biodegradability of cellulose acetate, but no review has been compiled which includes biological, chemical, and photo chemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
353
2
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 536 publications
(363 citation statements)
references
References 62 publications
5
353
2
3
Order By: Relevance
“…However, previous researches have shown that, cellulose acetate based materials were found to degrade underUV exposure at different wavelengths (i.e. 275-390 nm) in the presence of photo sensitizers and oxidation catalysts [17]. Thus, the objective of this study is to explore the effect of UVGI exposure within this context.…”
Section: Ultra Violet Germicidal Irradiationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, previous researches have shown that, cellulose acetate based materials were found to degrade underUV exposure at different wavelengths (i.e. 275-390 nm) in the presence of photo sensitizers and oxidation catalysts [17]. Thus, the objective of this study is to explore the effect of UVGI exposure within this context.…”
Section: Ultra Violet Germicidal Irradiationmentioning
confidence: 99%
“…bacteria and fungi) exist in both naturally occurring and commercially available bentonites [8] [5]. The biodegradation of cellulose acetate based material by soil microbes has been studied for a long time by number of authors [16] [17]. It is anticipated that, these microbes were responsible for the degradation of the membrane.…”
Section: Intrusion Of Pegmentioning
confidence: 99%
“…3 In the ensuing decades other polymers, such as acrylonitrile-butadiene-styrene (ABS), became more common for injection molding, although cellulose acetate, propionate, and butyrate esters have remained polymers of choice for certain items like eyeglass frames, screwdriver handles, and playing dice (Rustemeyer, 2004). Nearly 1.8 billion pounds of cellulose acetate were produced globally in 2008 and were destined for filter tow, textile threads, films, and molded plastic objects (Puls et al, 2010). Today, the polymer has the potential to increase its popularity as a renewable, plant-derived plastic that can be biodegraded under the right conditions (Puls et al, 2010;Laird, 2013;Solvay, 2013).…”
Section: Cellulose Acetate Plasticsmentioning
confidence: 99%
“…Nearly 1.8 billion pounds of cellulose acetate were produced globally in 2008 and were destined for filter tow, textile threads, films, and molded plastic objects (Puls et al, 2010). Today, the polymer has the potential to increase its popularity as a renewable, plant-derived plastic that can be biodegraded under the right conditions (Puls et al, 2010;Laird, 2013;Solvay, 2013).…”
Section: Cellulose Acetate Plasticsmentioning
confidence: 99%
“…It has no active function in cigarette smoke filtration; the titanium dioxide pigments are primarily used as delustering and whitening agent in the cellulose acetate fibers. As a photo-catalyst the pigments are also responsible for the photochemical degradation of the filter fibers (66). Activated carbon is another filter component influencing the composition of cigarette mainstream smoke.…”
Section: Reasons For the Use Of Tobacco Addi-tives In Cigarette Manufmentioning
confidence: 99%